ETHICS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS ON SOCIAL MEDIA: PROFESSIONAL AND PERSONAL BOUNDARIES IN THE DIGITAL ERA - Irsyad Kama Fahreza; Fahmi Maulana; Sri Wulandari; Muhlisin Muhlisin; Abul Mafaakhir (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
This study examines the boundaries of digital ethics for Islamic Religious Education teachers on social media, focusing on the tension between the professional and personal spheres in the contemporary digital ecosystem. Despite over 76% of Indonesian teachers actively using social media, governing regulations remain pre-digital and lack operational specificity, which represents a research gap that fundamentally motivates this inquiry. Employing a qualitative library research approach through thematic content analysis of 31 systematically selected sources based on rigorous inclusion and exclusion criteria from 380 identified references, this study yields three principal findings: (1) the absence of operationally relevant digital guidelines for teachers; (2) a typology of ethical violations comprising inappropriate content, unprofessional interactions with students, and disinformation dissemination rooted in mutually reinforcing structural, individual, and cultural factors; and (3) the tension between freedom of expression and professional responsibility cannot be resolved through regulatory means alone, but requires the strengthening of professional identity. As an original theoretical contribution, this article introduces the TAPAK Model (Responsibility, Accuracy, Respect, Audience, Context) as a reflective framework that explicitly addresses the context collapse mechanism, a critical dimension consistently overlooked in existing digital ethics models for teachers, both domestically and internationally.